Confinement effect and air tolerance of Li plating by lithiophilic poly(vinyl alcohol) coating for dendrite-free Li metal batteries. Issue 39 (26th September 2019) - Wu, Han; Yao, Zhenguo; Wu, Qingping; Fan, Shengsheng; Yin, Congling; Li, Chilin
Abstract : A highly tight poly(vinyl alcohol) coating on Cu foil or Li metal surface is introduced to achieve a superior confinement effect and long-term air tolerance of Li plating. Abstract : Lithium metal is an ideal anode material with high capacity and low redox potential, enabling the upgrade of energy density of batteries. However, the prevalence of dendritic and dead Li and resultant poor cycling performance have hindered its practical application. Herein, we introduced a highly tight poly(vinyl alcohol) (PVA) coating on Cu foil or a Li metal surface to achieve a superior confinement effect and long-term air tolerance of Li plating. This conformal and lithiophilic coating enables the compaction of Li deposits without evident grain boundaries and voids even at a high current density of 5 mA cm −2 . The PVA-protected Li anode can be exposed to air for at least one hour but still with evident metal glossiness, greatly improving its safety and operability. A high coulombic efficiency of ∼98% and long-term cycling of 250 cycles are preserved for modified Li/Cu and Li/Li cells, respectively, even at high 5–10 mA cm −2 . The facile strategy of conformal coating with high elasticity, tightness and robustness is a potential solution to high-stability Li anodes and high-rate Li–S batteries.